Verifying the Accuracy of Hemodynamic Analysis Using High Spatial Resolution 3D Phase-contrast MR Imaging on a 7T MR System: Comparison with a 3T System - Isoda, Haruo; Fukunaga, Masaki; Sadato, Norihiro; Tajima, Shunsuke; Naganawa, Shinji; Komori, Yoshiaki (Magnetic Resonance in Medical Sciences, 2025)
Purpose: Hemodynamics is important in the initiation, growth, and rupture of intracranial aneurysms. Since intracranial aneurysms are small, a high-field MR system with high spatial resolution and high SNR is desirable for this hemodynamic analysis. The purpose of this study was to investigate whether the accuracy of MR fluid dynamic (MRFD) results based on 3D phase-contrast MR (3D PC MR, non-electrocardiogram[ECG]-gated 4D Flow MRI) data from a human cerebrovascular phantom and human healthy subjects obtained by a 7T MR system was superior to those by a 3T MR system.Methods: 3D PC MR and 3D time of flight MR angiography (3D TOF MRA) imaging were performed on a 3T MR system and a 7T MR system for a human cerebrovascular phantom and 10 healthy human subjects, and MRFD analysis was performed using these data. The MRFD results from each MR system were then compared with the following items based on the computational fluid dynamics (CFD) results: 3D velocity vector field; correlation coefficient (R), angular similarity index (ASI), and magnitude similarity index (MSI) of blood flow velocity vectors.Results: In the MRFD results of 3D velocity vectors of the cerebrovascular phantom, noise-like vectors were observed near the vascular wall on the 3T MR system, but no noise was observed on the 7T MR system, showing results similar to those of CFD. In the MRFD results of the cerebrovascular phantom and healthy subjects, the correlation coefficients R, ASI, and MSI of the 7T MR system were higher than those of the 3T MR system, and ASI and MSI of healthy human subjects were significantly different between the two systems.Conclusions: The accuracy of high spatial resolution MRFD using the 7T MR system exceeded that of the 3T MR system.